Spontaneous hypoglycaemia due to a pleural fibroma: role of insulin like growth factors. - Masson, E A (1991)
A 64 year old woman with a long history of "drop attacks" and dizzy spells was found to have spontaneous hypoglycaemia. A slowly enlarging pleural mass had been present for at least five years. At thoracotomy the mass (weight 1.7 kg) was excised and the hypoglycaemia ceased. Histologically the tumour was a pleural fibroma, with no features of malignancy. Endocrine tests before surgery showed a subnormal growth hormone response to spontaneous hypoglycaemia, a reduced concentration of serum insulin like growth factor I (IGF-I), and an inappropriately high concentration of serum insulin like growth factor II (IGF-II). After resection of the tumour the growth hormone response to insulin induced hypoglycaemia and the IGF-I and IGF-II concentrations were normal. These data suggest that the hypoglycaemia was due to production of IGF-II by the tumour, causing increased glucose utilisation and an impaired growth hormone counterregulatory response to hypoglycaemia.